The Effect of CAMELS Ratio on Banking Distress in Private Banking Sector Listed on The IDX Period 2020 – 2022 - Vandana, Adelia Dinda Ayu; Kautsar , Achmad (Social Science Studies, 2023)
This study aims to determine the effects of CAMELS ratio analysis (Capital, Asset Quality, Management, Earnings, Liquidity, and Sensitivity to Market Risk) on Banking Distress in the private banking sector that is listed on the Indonesian Stock Exchange (IDX) for the period 2019 – 2021. The object of this research is 31 private banks, and the data collection technique uses a purposive sampling technique. The data source needed in the research is secondary data, which is annual financial statements from Indonesian Stock Exchange. This research is conclusive on causality by using the Logistic Regression Analysis technique on IBM SPSS tools version 29 software. The result shows that the variables Capital Adequacy Ratio (CAR) and Non-Performing Loans (NPL) have a positively significant effect on Banking Distress, while Operating Expenses to Operating Income (BOPO), Net Profit Margin (NPM), Return on Assets (ROA), Loan to Deposit Ratio (LDR), and Interest Rate Risk (IRR) have no significant effect on Banking Distress. This study can be a valuable reference for banking sectors in avoiding indicators leading to banking distress. Future researchers can develop the elements from this research, including a more expansive period of interval, carrying more varied independent variables from external factors, and using other more accurate models.